Correlation of Anxiety Level to Cimino Puncture Pain Intensity in Patients Undergoing Regular Hemodialysis - Marthalena Siahaan; Eka Isranil Laily; Donisman Bu'ulolo; Murni Aritonang (Jurnal Keperawatan Priority, 2026)
Patients with chronic kidney failure who undergo regular hemodialysis experience repeated cannulation of the arteriovenous fistula (Cimino), which produces pain arising not only from the physical trauma of needle insertion but also from the patient’s psychological state, particularly anxiety. This study aimed to analyze the correlation between anxiety level and pain intensity during Cimino puncture among regular hemodialysis patients at a hospital in Medan, Indonesia. A quantitative correlational design with a cross-sectional approach was used. Thirty-three respondents were recruited through purposive sampling. Anxiety was measured using the Hamilton Rating Scale for Anxiety (HRS-A), while pain intensity was assessed with the Numeric Rating Scale (NRS). Data were analyzed using the Spearman Rank correlation test. Most respondents experienced mild anxiety (78.8%), and pain intensity was predominantly moderate (57.6%). The Spearman Rank test showed a strong, statistically significant positive correlation between anxiety level and pain intensity (r = 0.590; p = 0.000; p < 0.05), indicating that higher anxiety was associated with greater pain during Cimino puncture. These findings confirm that psychological factors contribute meaningfully to the pain experienced during invasive hemodialysis procedures. Hemodialysis nurses are recommended to conduct routine anxiety assessment before Cimino cannulation and to apply non-pharmacological interventions, such as distraction and relaxation techniques, to reduce both anxiety and pain during the procedure.